1962
DOI: 10.1136/bmj.2.5305.633
|View full text |Cite
|
Sign up to set email alerts
|

Convulsions and Television Viewing

Abstract: MEASURING CO IN RESPIRED GASESPco2 are discussed. The most important practical conclusion is that the volume of gas in the bag should not be more than twice the tidal volume; but the exact ratio is not critical.Suitable equipment is described. Practical problems and variations in technique are described in detail.We are grateful to the many people who have told us of their experience and difficulties, and particularly to those who have suggested modifications and improvements. Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1963
1963
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Carterette and Symmes (1952) first reported that red flicker provoked an increased photo-convulsive response (PCR) relative to other wavelengths. Since then, this finding has been reported by Bickford (1953) ;Marshall, Walker, and Livingston (1953); Pantelakis, Bower, and Jones (1962); Kojima, Suguro, and Miyamoto (1963); Brausch and Ferguson (1965) ;Harley, Baird, and Freedman (1967); Tsukahara (1972a, 1973). It has also been reported by Carterette and Symmes (1952); Brausch and Ferguson (1965); Buskirk, Casby, Passouant, and Schwab (1952); Marshall et al (1953); Bickford (1954); Asano and Umezaki (1965); Maruyama and Maruyama (1968); Takahashi and Tsukahara (1972b) and Harley et al (1967) that red removing eyeglasses or contact lenses afforded clinical relief to patients with photogenic epilepsy.…”
Section: Apparatusmentioning
confidence: 53%
“…Carterette and Symmes (1952) first reported that red flicker provoked an increased photo-convulsive response (PCR) relative to other wavelengths. Since then, this finding has been reported by Bickford (1953) ;Marshall, Walker, and Livingston (1953); Pantelakis, Bower, and Jones (1962); Kojima, Suguro, and Miyamoto (1963); Brausch and Ferguson (1965) ;Harley, Baird, and Freedman (1967); Tsukahara (1972a, 1973). It has also been reported by Carterette and Symmes (1952); Brausch and Ferguson (1965); Buskirk, Casby, Passouant, and Schwab (1952); Marshall et al (1953); Bickford (1954); Asano and Umezaki (1965); Maruyama and Maruyama (1968); Takahashi and Tsukahara (1972b) and Harley et al (1967) that red removing eyeglasses or contact lenses afforded clinical relief to patients with photogenic epilepsy.…”
Section: Apparatusmentioning
confidence: 53%
“…As a television picture is produced by intermittent illumination, its effect on the viewer-especially one seated near to the screen-could be similar to that of intermittent photic stimulation used in medical practice for producing epileptic discharges. Pantelakis, Bower and Jones (1962) reported convulsions in children which were caused in television viewing. They further reported an incidence of television-induced epilepsy among epileptic children of 5.6%.…”
Section: Aspects Of Instructional Television Receiving Special Attentionmentioning
confidence: 98%
“…Details are given in our previous publication. 6 Briefly, one group of patients was more sensitive than the other, as shown by the presence in the one of EEG discharges with reduced flash intensity, of myoclonic jerking during I.P.S., and of marked epileptic discharges with eyes open. These features were, in general, absent in the less sensitive group.…”
Section: Bickford Et A13 Describe a Similar Casementioning
confidence: 99%